Batas Militar a documentary on Martial law in the Philippines - Apostol, Eugenia; Arroyo, Felicitas; Tiongson, Lito (The Foundation, 1998)
A documented video on the Martial law era, the principal players who lived through it, as well as the men and women who stood up to the dictatorship.